Diversity of coprophilous species of Panaeolus (Psathyrellaceae, Agaricales) from Punjab, India (Biodiversitas Journal of Biological Diversity, 2014)
Kaur A, Atri NS, Kaur M. 2014. Diversity of coprophilous species of Panaeolus (Psathyrellaceae, Agaricales) from Punjab, India. Biodiversitas 15: 115-130. An account of 16 Panaeolus species collected from a variety of coprophilous habitats of Punjab state in India is described and discussed. Out of these, P. alcidis, P. castaneifolius, P. papilionaceus var. parvisporus, P. tropicalis and P. venezolanus are new records for India while P. acuminatus, P. antillarum, P. ater, P. solidipes, and P. sphinctrinus are new reports for north India. Panaeolus subbalteatus and P. cyanescens are new records for Punjab state. A key to the taxa explored is also provided.
Keywords: Dung, epithelial pileus cuticle, systematics, taxonomy